Estimation of Stature from Index Finger Length and Sexual Dimorphism in Adult Chakma Males and Females (IAHS Medical Journal, 2022)
Background: Estimation of stature from index finger length in adult Chakma males and females and also to observe gender difference was the main purpose of this study.Materials and methods: It was a cross-sectional analytical study conducted over 104 adult healthy Chakma males and females (52 males and 52 females) residents of Chattogram Hill Tracts area in the year 2016 and 2017. Subject selection was done by convenience sampling technique and stature and index finger length were measured and data were documented in SPSS version 19.Results: A highly significant (p